Distorted planar defects stabilize tetragonal boron. (15th March 2021) - Zhang, Haibo; Shen, Yidi; Lahkar, Simanta; Fujita, Takeshi; Hemker, Kevin; An, Qi; Reddy, Kolan Madhav
Abstract: Tetragonal boron (T-B50 ) in elementary boron phases is suggested to be mechanically unstable due to the electron deficiency in icosahedral framework. Here we identified a unique distorted structure in T-B50 that stabilizes this phase by combining high-resolution transmission electron microscopy (HRTEM) and quantum mechanics (QM) simulations. Experimentally by using HRTEM in T-B50 crystal along 〈 101 〉 orientation, we show that large shear strain and lattice rotation at the proximity of planar faults stabilize the structure. QM simulations ascertained that the vacancy and shear deformation play an important role in the formation of the distorted structure observed experimentally. More interesting, QM simulations show that the distorted structure is similar in energy to the perfect tetragonal structure, but lower in energy than the vacancy structure. The origin of stabilization of distorted structure arises from satisfying the electron counting rule for B12 icosahedral clusters. Graphical abstract: Image, graphical abstract